2004
DOI: 10.1063/1.1634390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn interstitials on the lattice parameter of Ga1−xMnxAs

Abstract: Structural investigation of as-grown as well as annealed Ga 1-x Mn x As epilayers was carried out using high resolution X-ray diffraction (XRD) measurements for a wide range of Mn concentrations (0.027 ≤ x ≤ 0.083), with special attention on how the interstitial Mn atoms (Mn I ) influence the lattice parameter of this material. We observe a distinct decrease of the lattice parameter after low temperature annealing of Ga 1-x Mn x As, which is known to reduce the Mn I concentration. The reciprocal space maps mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 12 publications
6
36
2
1
Order By: Relevance
“…3, we show the influence of annealing on the lattice parameter of the 700 Å thick Ga 0.94 Mn 0.06 As layer (s2). As reported before 13,22 , one effect of post-growth annealing is a reduction of the (Ga,Mn)As lattice parameter. This is interpreted as an effect of removing Mn I atoms from the (Ga,Mn)As volume.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…3, we show the influence of annealing on the lattice parameter of the 700 Å thick Ga 0.94 Mn 0.06 As layer (s2). As reported before 13,22 , one effect of post-growth annealing is a reduction of the (Ga,Mn)As lattice parameter. This is interpreted as an effect of removing Mn I atoms from the (Ga,Mn)As volume.…”
mentioning
confidence: 85%
“…This is interpreted as an effect of removing Mn I atoms from the (Ga,Mn)As volume. Both experimental and theoretical studies 13,22,23 suggest that Mn interstitials are responsible for the observed lattice parameter increase in GaMnAs with Mn content, while substitutional Mn in Ga sites has only a small effect in this respect.The GaMnAs lattice parameter values calculated from angular positions of (004) Bragg diffraction peaks measured for as-grown as well as annealed pieces piece of s2 are given in Table 1. Thus, our results clearly indicate that Mn interstitials are removed from the (GaMn)As lattice by annealing under an As capping., in a similar way as by annealing in air or in nitrogen atmosphere, though on a shorter time scale than reported by Edmonds et.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) and (4); as-grown material with MnGa, Mnint, and AsGa (solid line), mixed crystal with all Mn int removed (dotted), material with the x i reduced to one third (dashed). ials [9][10][11] indicates that a large number of the compensating antisite defects (As Ga as well as some residual Mn int ) are present even in the best annealed samples with the minimum compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Problemas ocorrem quando, ao invés doíon Mn substituir umíon de Ga na rede, o Mn permanece em uma posição intersticial. Nesta configuração, ao invés de ser aceitador, oíon Mn passa a ser doador duplo, e além de não contribuir para o ferromagnetismo mediado por portadores (troca indireta), passa a acoplar antiferromagneticamente com os Mn substitucionais vizinhos [42]. Entrentanto, a técnica de post growth annealing permite remover grande parte dosíons Mn intersticiais, e desta forma, aumentar a qualidade das amostras.…”
Section: Gaasunclassified